Digital religion: How digital immigrants access religious content during pandemic - Sofia Aunul; Daniel Handoko (Islamic Communication Journal, 2022)
The Covid-19 pandemic has changed human interactions including how they carry out religious practices and this situation has made them change everything that the activities now through media. Digital immigrants aged from 38 years old and above categorized as generation born before digital era that requires them more to adopt the technology. This paper aims at how digital immigrants in Jakarta search for religious content during pandemic Covid-19. Media dependency theory is used in this research for analysing the research results. Media dependency theory has evolved with the changing communication environment and expanded its theoretical framework to communication infrastructure theory to cover new relationships between individuals and media. The research method used is qualitative descriptive of ten informants categorized as digital immigrants and data were collected through interview. The results found that the informants depended on digital media in searching for religious contents and participated on some religious circles in some digital (social) media platforms.***Pandemi Covid-19 telah mengubah interaksi manusia termasuk bagaimana mereka menjalankan praktik keagamaan dan situasi ini telah membuat mereka mengubah segala sesuatu yang aktivitasnya sekarang melalui media. Imigran digital berusia 38 tahun ke atas dikategorikan sebagai generasi yang lahir sebelum era digital yang menuntut mereka untuk lebih mengadopsi teknologi. Tulisan ini bertujuan untuk melihat bagaimana para imigran digital di Jakarta mencari konten religi di masa pandemi Covid-19. Teori ketergantungan media digunakan dalam penelitian ini untuk menganalisis hasil penelitian. Teori ketergantungan media telah berkembang dengan lingkungan komunikasi yang berubah dan memperluas kerangka teoretisnya ke teori infrastruktur komunikasi untuk mencakup hubungan baru antara individu dan media. Metode penelitian yang digunakan adalah deskriptif kualitatif terhadap sepuluh informan yang dikategorikan sebagai imigran digital dan data dikumpulkan melalui wawancara. Hasil kajian menemukan bahwa informan bergantung pada media digital dalam mencari konten keagamaan dan berpartisipasi pada beberapa kalangan keagamaan di beberapa platform media (sosial) digital.